Effect of zinc sulphate application and the cyclic incorporation of cereal straw on yields, the tissue concentration and uptake of Zn by crops and availability of Zn in soil under riceâwheat rotation - Rama Dwivedi; Prakash Chandra Srivastva (International Journal of Recycling of Organic Waste in Agriculture)
Background Soil incorporation of cereal straw to avoid burning and air pollution may influence the availability of Zn, a critical micronutrient in cereal production. Field experiment was carried out to evaluate the effect of zinc sulphate application and the cyclic incorporation of cereal straw on the yields, tissue concentration and uptake of Zn by rice and wheat crops and availability of Zn in soil. Results Application of 25 kg ZnSO4 ha-1 to I year rice crop increased the grain yields of rice by 24.3 and 56.3 % over control during I and II year, respectively. Application of 25 kg ZnSO4 ha-1 to I year rice crop ? cyclic incorporation of 1.5 t straw ha-1 increased the grain yields of rice by 21.4 and 87.4 % over control during I and II year, respectively. In I year, the grain yield of wheat crop was not significantly influenced by the different treatments while in II year the highest wheat grain yield was recorded with 25 kg ZnSO4 ha-1 to I year rice crop ? cyclic incorporation of 6.0 t cereal straw ha-1 . Application of 25 kg ZnSO4 ha-1 to I year rice ? cyclic incorporation of 1.5 t straw ha-1 resulted in a significant increase in the concentration of Zn in the plant tissues of both rice and wheat crops. The cyclic incorporation of 1.5â3.0 t cereal straw ha-1maintained better availability of ZnSO4 applied to I year rice crop to the subsequently grown crops. Conclusion Soil application of 25 kg ZnSO4 along with incorporation of 1.5 t cereal straw ha-1 prior to I year rice transplanting followed by cyclic incorporation of cereal straw in subsequent crops ensures higher availability of Zn in soil and higher yields in riceâwheat rotation.